2018
DOI: 10.1177/0021998318805201
|View full text |Cite
|
Sign up to set email alerts
|

Delamination resistance of composite laminated structures reinforced with angled, threaded, and anchored Z-pins

Abstract: The delamination resistance of Z-pinned laminates is directly dependent on the strength of the pin–laminate bonding at the interface. In this paper, we investigate novel approaches to the Z-pinning technology in order to increase delamination strength via enhancing mechanical interlocking of the pins. Toward this end, we study the effect of pin insertion at an angle to the vertical in contrast to the conventional vertical pin insertion. Subsequently, a novel variety of pin, namely the threaded pin, is studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…There are several methods available to mitigate the delamination issue [5], such as Z-pins or Z-anchoring (the introduction of thin pins, in the through thickness direction of the composite, holding the laminate plies together by a combination of adhesion and friction [6,7]), 3D weaving (the reinforcement of interlaminar properties by the creation of complex three dimensional dry fibre preforms before applying the resin [8,9]), stitching or tufting (embedding stitch threads through thickness direction, creating a bridging effect that will attenuate the delamination cracks [10,11]), mixed adhesive joints or functionally graded adhesive joints (to decrease of stress concentration at the ends of overlap and increase of joint strength using a more flexible adhesive at the ends of the overlap to reduce the peel stresses in that critical section [12,13]), and hybrid laminates (metal or polymeric laminates are used to reinforce the composite transversal properties [14][15][16][17]). The 3D weaving, stitching, braiding, tufting, z-pinning and z-anchoring techniques all successfully reduce delamination failure, but are quite laborious, which increases the cost of the final product [18].…”
mentioning
confidence: 99%
“…There are several methods available to mitigate the delamination issue [5], such as Z-pins or Z-anchoring (the introduction of thin pins, in the through thickness direction of the composite, holding the laminate plies together by a combination of adhesion and friction [6,7]), 3D weaving (the reinforcement of interlaminar properties by the creation of complex three dimensional dry fibre preforms before applying the resin [8,9]), stitching or tufting (embedding stitch threads through thickness direction, creating a bridging effect that will attenuate the delamination cracks [10,11]), mixed adhesive joints or functionally graded adhesive joints (to decrease of stress concentration at the ends of overlap and increase of joint strength using a more flexible adhesive at the ends of the overlap to reduce the peel stresses in that critical section [12,13]), and hybrid laminates (metal or polymeric laminates are used to reinforce the composite transversal properties [14][15][16][17]). The 3D weaving, stitching, braiding, tufting, z-pinning and z-anchoring techniques all successfully reduce delamination failure, but are quite laborious, which increases the cost of the final product [18].…”
mentioning
confidence: 99%
“…Among these methods, z‐pinning technique is especially suitable for the composite laminates made from prepreg materials, which may significantly increase the resistance against delamination crack. [ 14–16 ] The resultant interlamianr fracture toughness was improved remarkably by z‐pins. Fei et al [ 17 ] found that the z‐pinned composite with 0.11 mm z‐pin has a G IC value 11 times higher than that of the unpinned sample.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the characteristics of the laminates, FRP composites have high in-plane strength, but the out-of-plane properties are not as expected. Accordingly, many strategies, such as stitching [5,6], z-pinning [7][8][9], three-dimensional (3D) weaving [10,11], and matrix toughing [12,13], have been applied recently to improve the interlaminar strength of FRPs. Among these techniques regarding enhancing the out-of-plane properties of laminates, matrix toughing has received much attention, for the other ones remarkably decrease the in-plane strengths.…”
Section: Introductionmentioning
confidence: 99%